Association of Plate Contouring With Hardware Complications Following Mandibular Reconstruction. (24th June 2021) - Davies, Joel C.; Chan, Harley H. L.; Yao, Christopher M. K. L.; Ziai, Hedyeh; Dixon, Peter R.; Chepeha, Douglas B.; Goldstein, David P.; de Almeida, John R.; Gilbert, Ralph W.; Irish, Jonathan C.
Abstract : Objectives/Hypothesis: Despite considerable effort being dedicated to contouring reconstruction plates, there remains limited evidence demonstrating an association between contour and reconstructive outcomes. We sought to evaluate whether optimizing mandibular reconstruction plate contouring is associated with reduced postoperative hardware complications. Study Design: Retrospective cohort study. Methods: A cohort study was performed with adult patients (age ≥18 years) who underwent mandibulectomy and osseous free flap reconstruction following oncologic ablation at the University Health Network in Toronto, Canada, between January 1, 2003 and December 31, 2014. Patients with computed tomography scans performed within 1 year of reconstruction were included. Computer‐based three‐dimensional models were generated and used to calculate the mean plate‐to‐bone gap (mm). The primary outcome was plate exposure. Secondary outcome included a composite of plate exposure or intraoral dehiscence. Logistic regression models were fitted for each outcome accounting for other patient and surgical characteristics associated with the primary outcome. Results: Ninety‐four patients met inclusion criteria, with a mean age of 60.4 (standard deviation [SD] 14.9). The mean follow‐up time was 31.4 months (range 3–94). Reconstruction was performed with fibular (57%) and scapular free flaps (43%). In the multivariable model, small mean plate‐to‐bone gap (<1 mm) was independently associated with 86% reduced odds of plate exposure (odds ratio [OR] 0.12; 95% confidence interval [CI] 0.02–0.55). Mean plate‐to‐bone gap less than 1 mm was also independently associated with reduced odds of developing a composite of plate exposure or intraoral dehiscence (OR, 0.29; 95%CI, 0.11–0.75). Conclusion: Optimizing plate contouring during mandibular reconstruction may decrease the development of postoperative hardware complications. Level of Evidence: 4 Laryngoscope, 132:61–66, 2022